Ekspresi Sufistik Bentuk Pantun dan Syair dalam Puisi-Puisi Abdul Hadi W.M. - Sujarwoko, Sujarwoko; Kasnadi, Kasnadi; Suhartono, Suhartono (STKIP PGRI Ponorogo Press, 2024)
Sufistic expressions in poetry can be presented in various forms, including through pantun and poetry. These two forms in Sufi poetry are used as a means of accommodating Sufi ideas that describe the spiritual journey. The aim of this research is to find out the Sufistic expressions in the form of pantun and poetry in the poetry of Abdul Hadi W.M. This research uses a qualitative approach with the researcher as the main instrument. The data source for this research is the poetry of Abdul Hadi W.M. entitled: 1) “Madura”, Untuk Sebuah Catatan Harian, “Sajak-sajak Kelahiran”, “Jayakatwang”, and “Syair Berdua”. Meanwhile, the data for this research are poetry quotations that are in accordance with the research focus. Data collection using documentation techniques and data analysis techniques using descriptive and content analysis techniques. From the discussion it can be concluded that the Sufistic expression in the form of the sampiran pantun is used to describe nature which depicts peace of mind and the content part is to describe the actual state of a Sufi’s peace of mind. The poetry form is used as a means to describe the differences in the spiritual journey of mature saliks and those who are still learning.